Academic stress and burnout among primary school trainee teachers in the Rabat-Sale-Kenitra region - Bouhaba Abdelmounaim (EDP Sciences, 2021)
During the training phase, the trainee teacher seems to be more and more confronted with discomfort and stress, due to the accumulation of demands and obligations. Many of them are mostly unable to take it any longer, which makes them vulnerable to the burnout risk. This research aims to study the academic burnout of trainee teachers at the “Centre Régional des Métiers de l’Education et de la Formation “(CRMEF) of the Rabat-Sale-Kenitra region during 2019/2020. Four hundred and fifty trainee teachers responded to a self-questionnaire comprising the Maslach Burnout Inventory-Student Survey (MBI-SS) scale in its French version, as well as certain stress factors. In agreement with the literature, more than 60% of teachers show moderate and high levels of academic exhaustion, the main likely stressors presented are financial instability, and training overload. Many trainee teachers cannot cope with the burnout syndrome, which conducts to stress and absenteeism during the training, we hope that this study will lead to some practical solutions to prevent and reduce the risk of academic burnout.